Optical Fiber Sensing Cables for Brillouin-Based Distributed Measurements - Bastianini, Filippo (Sensors (Basel), 2019)
Brillouin distributed optical fiber sensing (Brillouin D-FOS) is a powerful technology for real-time in situ monitoring of various physical quantities, such as strain, temperature, and pressure. Compared to local or multi-point fiber optic sensing techniques, in Brillouin-based sensing, the optical fiber is interrogated along its complete length with a resolution down to decimeters and with a frequency encoding of the measure information that is not affected by changes in the optical attenuation. The fiber sensing cable plays a significant role since it must ensure a low optical loss and optimal transfer of the measured parameters for a long time and in harsh conditions, e.g., the presence of moisture, corrosion, and relevant mechanical or thermal stresses. In this paper, research and application regarding optical fiber cables for Brillouin distributed sensing are reviewed, connected, and extended. It is shown how appropriate cable design can give a significant contribution toward the successful exploitation of the Brillouin D-FOS technique.